Crystallization dynamics and interface stability of strontium titanate thin films on silicon. (1st April 2015) - Hanzig, Florian; Hanzig, Juliane; Mehner, Erik; Richter, Carsten; Veselý, Jozef; Stöcker, Hartmut; Abendroth, Barbara; Motylenko, Mykhaylo; Klemm, Volker; Novikov, Dmitri; Meyer, Dirk C.
<x xml:space="preserve">Abstract</x> Different physical vapor deposition methods have been used to fabricate strontium titanate thin films. Within the binary phase diagram of SrO and TiO2 the stoichiometry ranges from Ti rich to Sr rich, respectively. The crystallization of these amorphous SrTiO3 layers is investigated by in situ grazing‐incidence X‐ray diffraction using synchrotron radiation. The crystallization dynamics and evolution of the lattice constants as well as crystallite sizes of the SrTiO3 layers were determined for temperatures up to 1223 K under atmospheric conditions applying different heating rates. At approximately 473 K, crystallization of perovskite‐type SrTiO3 is initiated for Sr‐rich electron beam evaporated layers, whereas Sr‐depleted sputter‐deposited thin films crystallize at 739 K. During annealing, a significant diffusion of Si from the substrate into the SrTiO3 layers occurs in the case of Sr‐rich composition. This leads to the formation of secondary silicate phases which are observed by X‐ray diffraction, transmission electron microscopy and X‐ray photoelectron spectroscopy.